Left atrial wall thickness of the pulmonary vein reconnection sites during atrial fibrillation redo procedures. Issue 5 (24th April 2021) - Teres, Cheryl; Soto‐Iglesias, David; Penela, Diego; Jáuregui, Beatriz; Ordoñez, Augusto; Chauca, Alfredo; Huguet, Marina; Ramírez‐Paesano, Carlos; Oller, Guillermo; Jornet, Agustí; Palet, Jordi; Santana, David; et al.
Abstract: Background: Left atrial wall thickness (LAWT) has been related to pulmonary vein (PV) reconnections after atrial fibrillation (AF) ablation. The aim was to integrate 3D‐LAWT maps in the navigation system and analyze the relationship with local reconnection sites during AF‐redo procedures. Methods: Consecutive patients referred for AF‐redo ablation were included. Procedure was performed using a single catheter technique. LAWT maps obtained from multidetector computerized tomography (MDCT) were imported into the navigation system. LAWT of the circumferential PV line, the reconnected segment and the reconnected point, were analyzed. Results: Sixty patients [44 (73%) male, age 61 ± 10 years] were included. All reconnected veins were isolated using a single catheter technique with 55 min (IQR 47–67) procedure time and 75 s (IQR 50–120) fluoroscopy time. Mean LAWT of the circumferential PV line was 1.46 ± 0.22 mm. The reconnected segment was thicker than the rest of segments of the circumferential PV line (2.05 + 0.86 vs. 1.47 + 0.76, p < .001 for the LPVs; 1.55 + 0.57 vs. 1.27 + 0.57, p < .001 for the RPVs). Mean reconnection point wall thickness (WT) was at the 82nd percentile of the circumferential line in the LPVs and at the 82nd percentile in the RPVs. Conclusion: A single catheter technique is feasible and efficient for AF‐redo procedures. Integrating the 3D‐LAWT map into the navigation system allows a direct periprocedural estimation of the WT at any point of the LA. Reconnection points were more frequently present in thicker segments of the PV line. The use of 3D‐LAWT maps can facilitate reconnection point identification during AF‐redo ablation.